Cereblon deficiency ameliorates carbon tetrachloride-induced acute hepatotoxicity in HepG2 cells by suppressing MAPK-mediated apoptosis - Choi, Seo Young; Song, Parkyong; Hwang, Ji Sun; Lee, You Kyeong; Shin, Mi Song; Son, Hong-Joo; Kim, Yu-Jin; Kim, Wanil; Lee, Kwang Min (Frontiers in Immunology, 2024)
The liver is vulnerable to various hepatotoxins, including carbon tetrachloride (CCl4), which induces oxidative stress and apoptosis by producing reactive oxygen species (ROS) and activating the mitogen-activated protein kinase (MAPK) pathway. Cereblon (CRBN), a multifunctional protein implicated in various cellular processes, functions in the pathogenesis of various diseases; however, its function in liver injury remains unknown. We established a CRBN-knockout (KO) HepG2 cell line and examined its effect on CCl4-induced hepatocellular damage. CRBN-KO cells exhibited reduced sensitivity to CCl4-induced cytotoxicity, as evidenced by decreased levels of apoptosis markers, such as cleaved caspase-3, and aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities. CRBN deficiency enhanced antioxidant defense, with increased superoxide dismutase activity and glutathione ratios (GSH/GSSG), as well as reduced proinflammatory cytokine expression. Mechanistically, the protective effects of CRBN deficiency appeared to involve the attenuation of the MAPK-mediated pathways, particularly through decreased phosphorylation of JNK and ERK. Overall, these results suggest the crucial role of CRBN in mediating the hepatocellular response to oxidative stress and inflammation triggered by CCl4 exposure, offering potential clinical implications for liver injury in a wide range of liver diseases.